Skin Necrosis Resulting from Nontarget Embolization of the Falciform Artery during Transarterial Chemoembolization with Drug-Eluting Beads - Smith, Mitchell T.; Johnson, David Thor; Gipson, Matthew G. (Seminars in Interventional Radiology, 2015)
Intra-arterial embolic therapies are a mainstay of liver-directed therapies to palliate symptoms, improve survival, and bridge patients to transplantation. Vascular anatomy and type of embolic used can lead to complications of nontarget embolization with varying clinical consequences. This case report describes a rare, nontarget embolization of the falciform artery leading to supraumbilical skin necrosis.
Keywords: chemoembolization; complication; nontarget embolization; embolization; interventional radiology